8th AIAA Atmospheric and Space Environments Conference 2016
DOI: 10.2514/6.2016-3443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Prediction of Ice Shedding for a Full-Scale Heated Tail Rotor

Abstract: When helicopters are to fly in icing conditions, it is necessary to consider the possibility of ice shed from the rotor blades. In 2013, a series of tests were conducted on a heated tail rotor at NASA Glenn's Icing Research Tunnel (IRT). The tests produced several shed events that were captured on camera. Three of these shed events were captured at a sufficiently high frame rate to obtain multiple images of the shed ice in flight that had a sufficiently long section of shed ice for analysis. Analysis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It is also necessary to obtain data to improve and validate the model. A project was undertaken at NASA GRC to achieve these goals, which is documented in the literature [167,168] Once the images that contained a shed were identified, a four-point projective plane transformation was required to correct the perspective error of the camera on the ceiling.…”
Section: Shed Trajectory Predictionmentioning
confidence: 99%
“…It is also necessary to obtain data to improve and validate the model. A project was undertaken at NASA GRC to achieve these goals, which is documented in the literature [167,168] Once the images that contained a shed were identified, a four-point projective plane transformation was required to correct the perspective error of the camera on the ceiling.…”
Section: Shed Trajectory Predictionmentioning
confidence: 99%
“…For rotating components, although some conclusions made on stationary parts still hold, the freezing mechanism is complicated by centrifugal and Coriolis forces. Recently, several studies have documented the icing characteristics on rotating blades [11,12], and on rotating spinners [13][14][15][16]. Bidwell et al [13] found that the extent of icing of the spinner increases with the increase of droplet size, while that on the downstream components decreases.…”
Section: Introductionmentioning
confidence: 99%